1997
DOI: 10.1093/jn/127.7.1304
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Regulation of Classical Glutathione Peroxidase Expression Requires the 3′ Untranslated Region in Chinese Hamster Ovary Cells , ,

Abstract: Classical glutathione peroxidase (GPX) mRNA levels fall dramatically in selenium (Se)-deficient animals, but it is not known whether this mechanism is related to the mRNA 3' untranslated region (3'UTR) sequences that have been shown to direct Se incorporation. In this study, we used recombinant GPX constructs to investigate the role of the GPX 3'UTR in Se regulation of GPX mRNA levels in Chinese hamster ovary (CHO) cells. The CHO cells were transfected with GPX (pRc/GPX), GPX lacking the 3'UTR (pRc/Delta3'UTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…Half-maximal GPX1 mRNA levels occurred before 0.05 μg Se/g diet whereas half-maximal GPX activity levels occurred at 0.07 μg Se/g diet. In other studies with rats 6,24 and with cultured cells 20 we have shown that GPX1 mRNA levels clearly reach the plateau breakpoint at a lower Se level than for GPX activity. In the present study, we needed an intermediate dietary treatment between 0.05 and 0.1 μg Se/g diet to show more conclusively that GPX1 mRNA levels reach the plateau breakpoint before GPX activity.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Half-maximal GPX1 mRNA levels occurred before 0.05 μg Se/g diet whereas half-maximal GPX activity levels occurred at 0.07 μg Se/g diet. In other studies with rats 6,24 and with cultured cells 20 we have shown that GPX1 mRNA levels clearly reach the plateau breakpoint at a lower Se level than for GPX activity. In the present study, we needed an intermediate dietary treatment between 0.05 and 0.1 μg Se/g diet to show more conclusively that GPX1 mRNA levels reach the plateau breakpoint before GPX activity.…”
Section: Discussionsupporting
confidence: 48%
“…2,6,[14][15][16][17] Several studies have shown that GPX1 transcription is not affected by Se status, [17][18][19] indicating that Se status must regulate GPX1 mRNA stability. We have recently demonstrated that the GPX1 3' untranslated region (3'UTR) is necessary for GPX1 mRNA levels to decrease in Se-deficient cells, 20 suggesting that the GPX1 3'UTR may contain an Se-responsive element.…”
Section: Introductionmentioning
confidence: 99%
“…41 Dietary selenium stabilizes GPx mRNA 42 and the 3Ј untranslated region of the GPx gene plays an important role in GPx gene expression. 43 Enzyme activity of GPx is also upregulated by selenium in human cell lines. 44,45 There are only a few published studies on the in vitro effects of selenium on prostate cancer cell lines and most of them described an inhibitory effect of selenium on prostate cancer cells as an acute short-term effect.…”
Section: Effect Of Genistein On Antioxidant Enzymes Activities In Lncmentioning
confidence: 99%
“…A recent study has provided some experimental support for this hypothesis (Seyedali and Berry 2014) and earlier work showed that during Se deficiency, GPX1 mRNA, but not GPX4 mRNA, was targeted by NMD (Weiss and Sunde 1997;Moriarty et al 1998). However, there is also evidence that susceptibility of NMD is not sufficient to explain the variability of selenoprotein mRNA responses to Se deficiency.…”
Section: Introductionmentioning
confidence: 96%